ANATOMI BATANG AREN (ARENGA PINNATA MERR.) - Y I Mandang; Nenny S Sudarna (Jurnal Penelitian Hasil Hutan, 1989)
The  anatomical   features  of  aren stem  in relation  to  its utilization   were  studied   by  taking  samples  from  Bogor  Re- gency,   West Java.   The  mature  stem  has 8 to 10 m of clear bole with  30 to 43 cm  in diameter.  The hard pheripheral  region of  the stem  is only  0.5 to 5.2  cm in thickness   or 4 to 20 percent  of the .stem  volume.The pheripheral  region of  the stem  consists  largerly of fibrouascular  bundles  while  the central portion   consists  mainly bf parenchyma   tissues.  The frequency   of  vascular bundles  at pheripheral  region may  reach 139 bundle/sq.  cm  then gradually decreased  to 10 bundles/sq.   cm at the center.The  fiber  dimension   vary along and  across the  stem:   length  1618  to 2712  microns,  diameter.28   to 52 microns,  wallthickness  5 to 24 microns.   The Runhell  ratio varies from  0. 56 to 13.33.